Quantifying the Pain Experience in Hip and Knee Osteoarthritis - Rajiv Gandhi; Dmitry Tsvetkov; Herman Dhottar; J Roderick Davey; Nizar N Mahomed (Pain Research and Management)
PURPOSE: The present study investigated whether the conceptualization of hip and knee osteoarthritis pain implicit in the Western Ontario and McMaster Universities Arthritis Index (WOMAC) and Medical Outcomes Study Short-Form 36 (SF-36) scales is complete, or whether the addition of another scale, such as the Short-Form McGill Pain Questionnaire (MPQ-SF), provides a more complete characterization. Furthermore, the impact that mental health symptoms and catastrophizing had on these scales was investigated.